Integrasi Pendidikan Karakter dalam Pembelajaran Bahasa Indonesia di MI/SD - Rusdiono Mukri; Pirda Amaliyah (Prodi PGMI IAI Sahid, 2023)
The background of this research is that many students pay less attention to courtesy, lack respect for others, are less willing to share and help others, and are even more selfish. This study uses a library research research method. Information obtained from scientific books, research reports, scientific essays, theses and dissertations, regulations, statutes, yearbooks, encyclopedias, and other written and electronic sources. The data that has been collected is then analyzed. There are three findings in this research. 1) Character Education in Learning Indonesian Language Studies. 2) Integration of Character Education in learning Indonesian at school. 3) Barriers to Integrating Character Education in Indonesian Language Learning.